Pendidikan Kesehatan terhadap Personal Higiene Santri - Bintang Agustina Pratiwi; Oktarianita Oktarianita; Henni Febriawati; Nopia Wati; Nova Kartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of health education on the Personal Hygiene of students at the Pancasila Islamic Boarding School in Bengkulu City. This study is a quantitative study using a cross-sectional approach. The results of the univariate analysis obtained that the average score of personal hygiene behavior before being given health education was 42.17 and after health education was 61.20. In conclusion, there is an effect of health education on personal hygiene and on average before and after being given health education on personal hygiene behavior. Keywords: Health Education, Personal Hygiene